Steaming Maintains Fatty Acids, Antioxidants, and Proximate Content in Snack Bar Products from Cocoa Beans - Kasma Iswari; null Atman; Leni Marlina; null Riska; Sri Satya Antarlina; Ratna Wylis Arief; null Waryat; Rosniyati Suwarda; Noveria Sjafrina; Alvi Yani; null Sunarmani; Gabriel Herald Joseph; et al. (The Scientific World Journal)
Chocolate products on the market are generally in the form of chocolate bars as snacks made from cocoa powder. Fat and powder are separated first through a pressing process to obtain the cocoa powder. Cocoa powder loses most of its fat content during processing. Therefore, the study aimed to determine the effect of steaming time on the cocoa bean content of fatty acids, free fatty acids, proximate levels, and antioxidant activity of snack bar products made from steamed cocoa beans. Seven steaming time intervals for cocoa beans were studied. The results showed that a longer steaming time affects the fatty acids, saturated fatty acids, antioxidants, and proximate in cocoa beans. Steaming time treatment at 45 minutes increased oleic acid, palmitic acid, and antioxidant activity. In addition, reducing free fatty acids represents a quality improvement that meets international Codex Alimentarius standards, offering a competitive advantage in the market. The food industry can adopt this steaming technique to develop snack bars and new products that are healthier and more sustainable by using steaming as an effective processing method in maintaining and increasing the nutritional value of products.